Rwanda : Poverty Reduction Strategy Paper Annual Progress Report. (IMF Staff Country Reports; Country Report ;, 2005)
This paper examines the Annual Progress Report (APR) on Rwanda's Poverty Reduction Strategy Paper (PRSP). The 2004 APR is an important progress marker in Rwanda's long-term vision to reduce the proportion of Rwandans living below the poverty line from 60 percent to 25 percent and raise per capita incomes from USD 250 to above USD 1,000. It represents an analysis of progress to date under the 2002 PRSP and sets out in detail government initiatives, which contribute to the goal of poverty reduction.